2018
DOI: 10.37134/jrpptte.vol8.no2.3.2018
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of problem-solving efficacy among college Algebra students

Abstract: This paper discusses the development of the Problem -Solving Efficacy Scale on College Algebra. Through factor analytic research design, the scale underwent five development stages including assessment of factorability of the data, factor extraction, factor rotation and interpretation, rotation confirmation, and internal consistency analysis. In the 80item questionnaire administered to 80 randomly selected College Algebra students of Isabela State University, structural validity was attained with 34 scale item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As problems are unavoidable and a source of stress and anxiety, it is believed that teachers need to acquire problem-solving skills leading to the more effective utilization of IWBs. The study conducted by [15], which aimed to alleviate anxiety among College Algebra learners, demonstrates problem-solving efficacy. It may be argued that teachers should attempt positive problem orientation, so that they would be more likely to observe a problem as a challenge, suggesting that problems do exist, and should be addressed accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As problems are unavoidable and a source of stress and anxiety, it is believed that teachers need to acquire problem-solving skills leading to the more effective utilization of IWBs. The study conducted by [15], which aimed to alleviate anxiety among College Algebra learners, demonstrates problem-solving efficacy. It may be argued that teachers should attempt positive problem orientation, so that they would be more likely to observe a problem as a challenge, suggesting that problems do exist, and should be addressed accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…These people solve the problem with success. Literature also revealed that high self-efficacy promotes better performance in problem-solving [15]. However, people having negative problem orientation see the problem as a threat to one's own existence.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation